The morphologic correlation between vortex transformation and upper critical field line in opal-based nanocomposites - M. K. Lee (Nature Portfolio, 2021)
Abstract In this study, we investigate metallic nanocomposites to elucidate the properties of nanostructured conventional superconductors. Liquid tin, indium, and mercury are loaded into opal matrices by high pressure up to 10 kbar. The opal templates preserve the 3D dendritic morphology of confined superconducting metals to model a dendritic second phase with particular grain shape in bulk superconductors observed by a DualBeam microscope. We carry out measurements of the dc and ac magnetizations to study the superconducting phase diagrams, vortex dynamics, and impact of grain morphology in the opal composites. Besides, we apply the small-angle neutron scattering (SANS) to deny a regular vortex structure. The phase diagrams reveal an enhanced upper critical field H c2(0) and curvature crossover in the upper critical field line. We also calculate the vortex activation barriers U a and observe a transformation in the vortex system. According to the field dependence of U a , the vortex structure transformation highly correlates with the curvature crossover in the upper critical field line. Our observations suggest that the similarity in the normalized phase diagrams and field dependences of U a in the three nanocomposites is owing to their particular morphology of confinement.